Post 9/11 Afghan Women: A Comparative Study Of Khaled Hosseini And Atique Rahimi’s Writings - Anwar, Saima; Fida, Sadia (School of Social Sciences, USM, 2017)
Afghanistan is a country that has been facing war for about 40 years. Women and children have always been the victims of this war and its spoils. In their narratives, both the novelists Khaled Hosseini and Atique Rahimi present a subjective vision of post 9/11 Afghan women and thereby attempt to awaken the world to the plight of deprived women in Afghanistan. In this qualitative research, Catherine Belsey’s theory of Expressive realism has been applied on Khaled Hosseini and Atique Rahimi’s works to find out the answer of the question: What was the condition of Afghan women in Pre- Taliban and Post-Taliban eras as portrayed in the selected novels of the selected writers Khaled Hosseini and Atique Rahimi ?The aim of the research is to explore whether women are oppressed in Afghan society or not, and whether the incident of 9/11 and US bombing of Afghanistan improved the miserable predicament of Afghan women or not. The research would be helpful to locate the social position of women in Afghan society under the rule of Taliban and then finally in post 9/11 Afghanistan.